PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING MELALUI PENDEKATAN BERDIFERENSIASI MENGGUNAKAN BLENDED LEARNING TERHADAP HASIL BELAJAR SISWA PADA KONSEP FISIKA DI SMA NEGERI 6 GORONTALO UTARA - Anatasya Lagarusu; Abdul Haris Odja; Citron S. Payu (Jurnal Pendidikan Fisika Undiksha, 2023)
This study aims to determine the effect of the problem-based learing model through a differentiated approach using blended learning on student learning outcomes in the concept of physics at SMA Negeri 6 Gorontalo Utara. This research method is an experimental research. This type of research is a quasi-experimental( quasi-experimental design.The design used was the Pretest-Posttest Only Control Grub Design. The population of this research was all student in class XI MIPA 2 and class XI MIPA 3 with the sampling technique being purposive sampling.The results of the analysis of hypothesis testing for the experimental and control classes t count> t table for the leve a = 0,05. the average obtained in the experimental class wa 87,18 and 58,5 in the control class. It can be concluded that there is an influence of the problem-based learning model through a differentiated approach to student learing outcomes.